Microstructural and Mechanical Analysis of Aluminum Joints Under Varying Rotational Speeds in Friction Welding with Post-Quenching - Bibit Sugito; Agus Dwi Anggono; Agung Setyo Darmawan; Agus Hariyanto (Engineering Proceedings, 2025)
This study examines the effects of rotational speed and post-weld quenching on aluminum friction-welded joints’ microstructure, hardness, and mechanical properties. Tests were conducted at rotational speeds of 1250 rpm, 1350 rpm, and 1450 rpm, with elemental composition assessed via SEM–EDS, and the hardness and mechanical properties were measured. The results showed that aluminum (Al) was the primary element in all samples. Hardness increased with rotational speed, reaching 70 VHN at 1250 rpm, 80 VHN at 1350 rpm, and 81 VHN at 1450 rpm. The highest stress was recorded at 1350 rpm, with the lowest at 1450 rpm. The aluminum joints exhibited high stress and strain values, confirming their ductile nature. These findings highlight the significant influence of rotational speed and quenching on friction-welded aluminum’s microstructural and mechanical behavior, providing insights for optimizing welding parameters for improved material performance in industrial applications.